MODIFIKASI ZEOLIT ALAM DENGAN CETILTRIMETILAMMONIUM BROMIDA DAN APLIKASINYA UNTUK ADSORPSI ION Cu2+, SO42- DAN ZAT WARNA ANIONIK METIL MERAH - , MARIYAH AGNES; , Dr. Sutarno, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The study modification of Klatenâs natural zeolite has been performed. In order to achieve a positive external surface of the zeolite. The negative surface was modified using Cetyltrimetihylammonium Bromide (CTAB). Modified zeolite then used to adsorb Cu 2+ , SO4 2- and methyl red anionic dye. The study began with zeolite activation by washing natural zeolite using aquadest, and then followed by reflux with 3 M Hydrocloric acid. Activated zeolite was modified by CTAB. Surfactant modified zeolite by CTAB (SMZ-CTAB) was applied for sorption of Cu 2+ , SO4 2- and methyl red anionic dye. Zeolite samples were characterized by FTIR and XRD method, while unadsorbed concentration of Cu 2+ cation, SO4 2- anion and methyl red anionic dye were determined by atomic absorption spectroscopy (AAS) and UV-Vis Spectrophotometer. The results showed that the adsorption of Cu 2+ cation, SO4 2- anion and methyl red anionic dye on SMZ-CTAB followed the Langmuir adsorption isotherm. The adsorption capacity of SMZ-CTAB for SO4 2- anion was higher than Cu 2+ cation and methyl red anionic dye with the adsorption capacity 1.11 x10 -5 mol g -1 for SO4 2- anion, 0.84 x10 -5 mol g -1 for Cu 2+ cation and 0.71 x10 -5 mol g -1 for methyl red anionic dye, respectively.